The Coseismic Ionospheric Disturbance During 2023 Turkey Double Earthquake Monitored by GNSS Observations - Yongxin Chen; Keke Wang; Wei Li; Xiaoxia Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The global navigation satellite system observations can invert the characteristics of global ionospheric changes, which help understand the coupled physical processes in the atmosphere caused by earthquakes. On 6 February 2023, Turkey experienced two strong earthquakes: an Mw7.8 event at UTC 01:17:34 and an Mw7.5 event at UTC 10:24:50. The propagation direction of ionospheric disturbances aligns with the rupture zones, which are bidirectional northeast–southwest ruptures for the first event and east–west ruptures for the second one. According to the results of Turkey stations, it is found that the coseismic ionospheric disturbances (CIDs) of the first earthquake are primarily driven by acoustic waves, but there are also Rayleigh waves and mixed waves’ components. Due to the influence of the first earthquake and aftershocks, the CIDs of the second earthquake are dominated by acoustic waves and Rayleigh waves. Notably, the Mw7.5 earthquake resulted in stronger ionospheric disturbance amplitudes than the Mw7.8 event, while the Mw7.8 event affected a larger spatial disturbance area. Meanwhile, it is confirmed that significant CIDs will be detected when the strike-slip earthquake magnitude is large enough.